2021
DOI: 10.1007/s00062-021-01051-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Cerebral Aneurysm Rupture in Mongolia

Abstract: Purpose Identification of country-specific demographic, medical, lifestyle, and geoenvironmental risk factors for cerebral aneurysm rupture in the developing Asian country of Mongolia. First-time estimation of the crude national incidence of aneurysmal subarachnoid hemorrhage (aSAH). Methods A retrospective analysis of all intracranial digital subtraction angiographies (DSA) acquired in Mongolia during the 2‑year period 2016–2017 (1714 examinations) was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…A similar trend was also observed in the control group. Previous studies have reported that approximately 20–30% of patients with IA have multiple aneurysms [ 2 , 27 ]. The PCoA was frequently associated with multiple IAs and was found to be an independent predictor of rupture in multiple IAs [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A similar trend was also observed in the control group. Previous studies have reported that approximately 20–30% of patients with IA have multiple aneurysms [ 2 , 27 ]. The PCoA was frequently associated with multiple IAs and was found to be an independent predictor of rupture in multiple IAs [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…41%, 46%, and 60%, respectively [5]. In a recent study by Bechstein et al [6], it was reported that Mongolia reported a crude incidence of 14.53 ruptures per 100,000 persons.…”
Section: Introductionmentioning
confidence: 96%